PENGARUH BAHAN ANTIKARIES BEBERAPA TANAMAN HERBAL YANG DIKOMBINASI DENGAN PASTA GIGI YANG MENGANDUNG FLUORIDE TERHADAP PERTUMBUHAN STREPTOCOCCUS MUTANS SECARA IN VITRO: ANTICARIES EFFECT OF SOME HERBAL PLANTS COMBINED WITH FLUORIDE TOOTH PASTE ON THE GROWTH OF STREPTOCOCCUS MUTANS - Santi Chismirina; Sri Rezeki; Cut Reinilda Rischa (Dentika: Dental Journal, 2010)
Dental caries is the most commonly oral disease and the main bacterial cause of it is Streptococcus mutans (S. mutans). Fluoride, xylitol, betel leaf and siwak are the substances often found in toothpaste. The effect of them inhibits the growth of S. mutans. The purpose of this study was to determine the effect of herbal plants such as xylitol, betel leaf and siwak that combined with fluoride in toothpaste on the growth of S. mutans (in vitro). S. mutans laboratory strain was exposed to three toothpastes that contained combination of fluoride and each of herbal plants such as xylitol, siwak, and betel leaf. This study also used non herbal toothpaste as a control. The results of ANOVA test on S. mutans colonies growth in media TYS20B showed that there was significant difference (p<0.05) between the types of herbals contained of fluoride toothpaste in reducing the number of S. mutans colonies. Duncan test showed that combination of fluoride and siwak was significant difference from others. It showed that toothpaste containing fluoride and siwak with the average number of S. muntans colonies of 23.44 CFU/ml, 31 CFU/ml toothpaste containing fluoride and betel leaf. The smallest influence was found in toothpaste that contained fluoride and xylitol with the average number of colonies of S.mutans is 32.67 CFU/ml. It was concluded that combination of fluoride and siwak in toothpaste has a higher effect in decreasing S. mutans colonies growth. This is apparently due to the function of isothiocyanate, flavonoid and tannin in siwak as anti-microbial, besides the existence of fluoride in siwak is also suspected to increase the effectiveness of toothpastes containing fluoride. As conclusion, additional of herbal plants such as xylitol, betel leaf and siwak in toothpaste that contained combination of fluoride increase the effect of toothpaste inhibit S. mutans colonies growth compared to toothpaste that only contained fluoride.